The chemical class of quinazoline compounds provides a core structure for the design of anticytomegaloviral kinase inhibitors - Hutterer, Corina; Hamilton, S.; Steingruber, Mirjam; Zeitträger, Isabel; Bahsi, Hanife; Thuma, Natalie; Naing, Z.; Oerfi, Z.; Oerfi, L.; Socher, Eileen; Sticht, Heinrich; Rawlinson, W.; et al. (Antiviral Research, 2016)
HCMV is a member of the family Herpesviridae and represents a worldwide distributed pathogen with seropositivity rates in the adult population ranging between 40% and 90%. Notably, HCMV infection is a serious, sometimes life-threatening medical problem for newborns and immunosuppressed individuals, including transplant recipients and patients under antitumoral chemotherapy. Current standard therapy with valganciclovir has the disadvantage of inducing drug-resistant virus mutants and toxicity-related side effects. Our analysis stresses the earlier finding that kinase inhibitors of the quinazoline class exert an antiviral response by targeting the viral protein kinase pUL97 without inducing resistance. Therefore, quinazolines have been used as a core structure to gain insight in the mode of inhibitor-kinase interaction. Here, we demonstrate that (i) the novel quinazolines Vi7392 and Vi7453 are highly active against HCMV laboratory and clinically relevant strains including maribavir- and ganciclovir-resistant variants, (ii) antiviral activity is not cell-type specific and was also detected in a placental explant tissue model using a genetically intact HCMV strain (iii) the viral kinase pUL97 represents a target of the anticytomegaloviral activity of these compounds, (iv) induction of pUL97-conferring drug resistance was not detectable under single-step selection, thus differed from the induction of ganciclovir resistance, and (v) pUL97 drug docking simulations enabled detailed insights into specific drug-target binding properties providing a promising basis for the design of optimized kinase inhibitors. These novel findings may open new prospects for the future medical use of quinazoline drug candidates and the use of drug-target dynamic simulations for rational design of antivirals.
Keywords: Antiviral drug target; Homology model of pUL97; Human cytomegalovirus; pUL97 drug docking simulation; Quinazoline compounds; Viral kinase pUL97